Analysis of indicators of the state of organs and tissues of oral cavity of caries-resistant and caries-liable persons in the dynamics of preventive measures - N. I. Mikheykina (Acta Biomedica Scientifica, 2015)
A promising direction of dental caries prevention is the use of funds on the basis of calcium, phosphorus and fluorine. In this regard the first step of increasing the resistance of enamel to the action of organic acids formed during the fermenting soft plaque are designed to be caries-preventive activities that contribute to the increase of calcium and phosphorus in the crystal lattice of enamel. In the article a comparison of indicators characterizing the state of the organs and tissues of the mouth of caries-resistant and caries-liable persons before and after courses of preventive measures. Differences in indicators of the condition of dental enamel, periodontal and level of oral hygiene and anticariogenic plaque will optimize the processes of prevention, maximally individualize the purpose of caries-preventive funds.